FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGUNJUNG DAMA RESTO TERHADAP PROTOKOL KESEHATAN SEBAGAI UPAYA PENCEGAHAN COVID-19 TAHUN 2020 - Tiara Raudha Fanela, (2021)
Corona Virus Disease 2019 (COVID-19) is an infectious disease caused by a new type of coronavirus, namely Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). To prevent COVID-19, it is necessary to implement health protocols. The purpose of this study was to analyze and examine factors related to compliance of Dama Resto's visitors with health protocols as an effort to prevent COVID-19 in 2020. This research was conducted in Dama Resto, Solok Regency, West Sumatra using a quantitative research design with cross-sectional analytical method. This study used accidental sampling technique with 312 samples. The instruments in this study were the observation sheet checklist and questionnaire. The results showed that some respondents did not comply with health protocols (86.2%). Based on the bivariate analysis using the chi-square test, the factors that have significant relationships with adherence to health protocols are attitude, facilities at Dama Resto, family support, and Dama Resto employees' support (p-value <0.05). Meanwhile, gender, knowledge, and government support did not have significant relationship with adherence to health protocols as an effort to prevent COVID-19. Therefore, Dama Resto was advised to form a team responsible for implementing health protocols and respondents were advised to apply health protocols properly.